Safety and Effectiveness of the Hyaluronic Acid Dermal Filler VYC-17.5L for Nasolabial Folds: Results of a Randomized, Controlled Study. Issue 5 (May 2018) - Monheit, Gary; Beer, Kenneth; Hardas, Bhushan; Grimes, Pearl E.; Weichman, Barry M.; Lin, Vince; Murphy, Diane K.
Abstract : BACKGROUND: Juvéderm Vollure XC (VYC-17.5L) belongs to a family of nonanimal hyaluronic acid (HA) gels based on the Vycross technology platform. OBJECTIVE: To evaluate the safety and effectiveness of VYC-17.5L for correction of moderate to severe nasolabial folds (NLFs) compared with a control HA dermal filler. METHODS: In this double-blind study, 123 adults with 2 moderate or severe NLFs as measured on the 5-point photonumeric NLF severity scale (NLFSS) were randomized to VYC-17.5L in 1 NLF and control in the contralateral NLF. The coprimary effectiveness end points at Month 6 were difference in improvement in mean NLFSS score for VYC-17.5L versus control and NLFSS responder rate (≥1-point improvement) for VYC-17.5L. RESULTS: The coprimary effectiveness end points were met. NLFSS scores improved by 1.4 with VYC-17.5L and by 1.3 with control; NLFSS responder rate with VYC-17.5L was 93.2%. More than three-quarters of subjects (82%) treated with VYC-17.5L were very satisfied at Month 6. Investigators reported that VYC-17.5L was smoother and more natural looking and easier to inject and mold than control. VYC-17.5L resulted in significantly fewer severe injection site responses than control. CONCLUSION: VYC-17.5L was safe and effective for correcting moderate to severe NLFs, with results lasting through 6 months in 93% of subjects.